Two-Class Neoclassical Growth–A Conjecture Proved - Rau, Nicholas (Quarterly Journal of Economics, 1975)
Journal Article Two-Class Neoclassical Growth — A Conjecture Proved Get access Nicholas Rau Nicholas Rau University College London Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 89, Issue 2, May 1975, Pages 344–345, https://doi.org/10.2307/1884441 Published: 01 May 1975